Facile Access to Ring-Fused Aminals via Direct α-Amination of Secondary Amines with ortho-Aminobenzaldehydes. Synthesis of Vasicine, Deoxyvasicine, Deoxyvasicinone, Mackinazolinone and Ruteacarpine - Richers, Matthew T. (2013)
Secondary amines undergo redox-neutral reactions with aminobenzaldehydes under conventional and microwave heating to furnish polycyclic aminals via amine α-amination/N-alkylation. This unique α-functionalization reaction proceeds without the involvement of transition metals or other additives. The resulting aminal products are precursors for various quinazolinone alkaloids and their analogues.